Pengaruh Efikasi Diri dan Minat Belajar Terhadap Kemampuan Pemecahan Masalah Matematika di SMP Negeri Jakarta Barat Dua - Ananda, Chevin; U.S, Supardi; Alfin, Edward (ALFARISI: Jurnal Pendidikan MIPA, 2026)
Method research the used is method the survey correlation statistics analysis of path (Path Analysis). The sample taken as much as 88 people students the taken the random simple. Collection the data carried out with test and spread questionnaire direct to the sample. Analysis of the data using the statistics descriptive like looking for the mean, median, mode, the standard deviation, and statistics inferential. Results research show: 1) There are influence direct the significant Efficacy self to ability Solving The problem mathematics junior high school country in Western Jakarta 2. It the evidenced with acquisition the value of 𝑆𝑖𝑔. = 0.000 < 0,05 and 𝑡ℎ𝑖𝑡𝑢𝑛𝑔 = 6,393. 2) There are influence direct the significant Interest learning to ability solving the problem mathematics junior high school Country in western Jakarta 2. It the evidenced with acquisition the value of 𝑆𝑖𝑔 = 0.000 < 0,05 and 𝑡ℎ𝑖𝑡𝑢𝑛𝑔 = 5,872; 3) There are influence direct the significant Efficacy Self to Interest learning Junior high school Country in western Jakarta 2. It the evidenced with acquisition the value of 𝑆𝑖𝑔 = 0.000 < 0,05 and 𝑡ℎ𝑖𝑡𝑢𝑛𝑔= 46,827; and 4) There are influence not direct the significant Efficacy Self through the Interest learning To The ability Solving The problem Mathematics Junior high school Countryin western Jakarta 2. It the evidenced with acquisition the value of 𝑡ℎ𝑖𝑡𝑢𝑛𝑔 > 𝑡𝑡𝑎𝑏𝑒𝑙 (7,166 > 1, 988). Research this showing that improvement Efficacy self students need to off set with effort Grow interest learning in order to students able to increase the ability solving the problem mathematics students.
Keywords: Efikasi Diri; Minat Belajar; Kemampuan Pemecahan Masalah ,Matematika